1969
DOI: 10.1111/j.1469-7998.1969.tb01716.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of photoperiod and temperature on testicular recrudescence and body growth in the lizards, Lacerta sicula and Lacerta muralis

Abstract: With 1 plate and 16 figures in the text)Annual testicular cycles in the lizards Lacerta sicula and L. muralis appear to be regulated by the interaction between seasonal changes in body temperature and an endogenous rhythmicity in thermal responsiveness. Photoperiodism does not appear to be an important factor; i.e. testicular activity does not appear to be regulated by daylength.Following testicular regression in July, the lizards are refractory to sexual Stimulation by high temperatures (i.e. normal preferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1969
1969
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The spermatogenic cycle of Po d arcis vaucheri is of the "mixed-type", in agreement with what is the dominant pattern in temperate lizards (Licht et al, 1969;SaintGirons, 1982;Carretero, 2006), especially those belonging to the genera Lacerta s.l. and Po d arcis (Saint-Girons Duguy, 1970;Angelini et al, 1979;HraouiBloquet, 1985;Hraoui-Bloquet Bloquet, 1988;BraÑa et al, 1990;Castilla Bauwens, 1990;Galán, 1996;Amat et al, 2000;Roig et al, 2000;Carretero et al, 2006a).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The spermatogenic cycle of Po d arcis vaucheri is of the "mixed-type", in agreement with what is the dominant pattern in temperate lizards (Licht et al, 1969;SaintGirons, 1982;Carretero, 2006), especially those belonging to the genera Lacerta s.l. and Po d arcis (Saint-Girons Duguy, 1970;Angelini et al, 1979;HraouiBloquet, 1985;Hraoui-Bloquet Bloquet, 1988;BraÑa et al, 1990;Castilla Bauwens, 1990;Galán, 1996;Amat et al, 2000;Roig et al, 2000;Carretero et al, 2006a).…”
Section: Discussionsupporting
confidence: 60%
“…Besides the environmental conditions, several studies showed reproductive cycles to be influenced also by the interaction between endogenous and exogenous factors (Licht et al, 1969;Licht, 1972;Angelini et al, 1976;Lofts, 1978;Marion, 1982;Jenssen Nunez, 1994;Carretero, 2006). On one hand, indeed, the gonadal and hormonal activity can be considered the main endogenous mechanisms controlling reproductive cycles (Díaz et al, 1994;Ikeuchi, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In dissociated breeders (i.e., where gonadal recrudescence occurs either in the fall or winter leading up to spring mating, Van Dyke 2014 ), a prolonged cold period prior to the onset of warm temperatures is a prerequisite to recrudescence and associated reproductive behaviors (Marion 1982 ; Gavaud 1991 ; Lutterschmidt 2012 ), with photoperiod having little to no effect (Aldridge 1975 , 1979 ). Even in species that do not rely on a cold period to trigger recrudescence, gradual warming in late winter and early spring is still the primary cue stimulating reproduction (Tinkle and Irwin 1965 ; Licht et al 1969 ). Evidence from laboratory manipulation experiments implicates the action of environmentally sensitive hormones in entraining biological rhythms to overwinter thermal conditions.…”
Section: Reptile Winter Ecology and Predictions Under Winter Warmingmentioning
confidence: 99%